"Epistemologi Hukum Islam dalam Bingkai Kaidah اليقين لا يزال بالشك" - Elvira Rosiana Indah; Nur Rahmawati Wahid; Wahyu Adi Nugroho; Muh Zamroni (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The fiqh principle “اليقين لا يزال بالشك” (faith is not lost due to doubt) is a basic principle in Islamic law that aims to ensure legal certainty in various aspects of life. This study attempts to explore the epistemological basis of this principle by examining its definition, textual basis, and practical application in the context of state governance. This study uses a normative method through literature review and comparative analysis. The research findings show that this principle plays an important role in the legal system, especially in upholding the principle of presumption of innocence, policy consistency, and legal protection of citizens. However, there are several exceptions in its application, such as in ritual worship, social transactions (muamalah), emergency conditions, and the issuance of religious fatwas. This study concludes that although Islamic law emphasizes certainty, it still maintains adaptive flexibility in responding to the changing realities of society.